Use of SADARI Educational Video Media on the Knowledge and Attitudes of Menopausal Women - Widya Ananda Arifin; Khasanah, Uswatun; Esyuananik, Esyuananik; Wahyu Wulan, Dwi (Universitas Nahdlatul Ulama Surabaya, 2025)
Indonesia ranks eighth in the number of cases of breast cancer in Southeast Asia. Deaths are rising as 70% of detections are in advanced stages. Low knowledge leads to a woman who doesn't know there are bumps on her breasts. So, we need health promotion. For menopause, breast checks themselves (SADARI) are done every month on the same date, but still, many do not apply SADARI. Objective: This study is intended to analyze the use of SADARI Educational Video Media for SADARI Knowledge and Attitudes in menopausal women. Quantitative research, with design pre-experiment one group pre-post-test, research carried out in Dusan Bluru Kidul, Sidoarjo, Sampling technique using simple random sampling of 38 women menopause, Primary data collection technique with instrument questionnaire knowledge and attitude SADARI. Data analysis technique using Wilcoxon Signed Rank Test. Results show p-value 0,000 (<0,05), which means there is an increase in knowledge from less to sufficient and suitable, negative attitude to positive after displayed educational media video SADARI in menopausal women. So, it can be concluded that educational video media about SADARI can be used to improve the knowledge and attitudes of menopausal women. It's expected that menopausal women can do a monthly routine as early detection.